CRISPR-based resistance to grapevine virus A - Spencer, Katarina P.; Burger, Johan T.; Campa, Manuela (Frontiers in Plant Science, 2023)
Grapevine (Vitis vinifera) is an important fruit crop which contributes significantly to the agricultural sector worldwide. Grapevine viruses are widespread and cause serious diseases which impact the quality and quantity of crop yields. More than 80 viruses plague grapevine, with RNA viruses constituting the largest of these. A recent extension to the clustered regularly interspaced, short palindromic repeat (CRISPR) armory is the Cas13 effector, which exclusively targets single-strand RNA. CRISPR/Cas has been implemented as a defense mechanism in plants, against both DNA and RNA viruses, by being programmed to directly target and cleave the viral genomes. The efficacy of the CRISPR/Cas tool in plants is dependent on efficient delivery of its components into plant cells. To this end, the aim of this study was to use the recent Cas13d variant from Ruminococcus flavefaciens (CasRx) to target the RNA virus, grapevine virus A (GVA). GVA naturally infects grapevine, but can infect the model plant Nicotiana benthamiana, making it a helpful model to study virus infection in grapevine. gRNAs were designed against the coat protein (CP) gene of GVA. N. benthamiana plants expressing CasRx were co-infiltrated with GVA, and with a tobacco rattle virus (TRV)-gRNA expression vector, harbouring a CP gRNA. Results indicated more consistent GVA reductions, specifically gRNA CP-T2, which demonstrated a significant negative correlation with GVA accumulation, as well as multiple gRNA co-infiltrations which similarly showed reduced GVA titre. By establishing a virus targeting defense system in plants, efficient virus interference mechanisms can be established and applied to major crops, such as grapevine.